Application of Food Mechanics and Oral Processing in Modelling First Bite of Grilled Meat - Ilija V. Djekic; Jovan G. Ilic; Bartosz G. Sołowiej; Rastko I. Djekić; Igor B. Tomasevic (Journal of Food Quality)
This study analyzed the potential of modelling meat mastication by using pork and poultry meat as food with different physical properties under different grilling temperatures. For the purpose of modelling oral processing, temporal dominance of sensations and finite element methods were employed. A panel with ten subjects was trained and used for oral processing analysis and temporal dominance of sensations revealing in-mouth sensations and mastication characteristics. In parallel, the second aim was to evaluate the mechanical properties of the samples and explore the potential of simulating the first bite using the finite element method. Based on the textural parameters, a 3D model of grilled meat was created and a first-bite simulation was performed. A higher level of differences was observed comparing the number of chews for pork meat compared to poultry meat. The chewing rate showed a statistical difference with values in the range of 1.31 chews/s to 1.46 chews/s for pork meat and between 1.36 chews/s and 1.42 chews/s for poultry meat. Firmness was the predominant sensory attribute recognized by panelists at the beginning of mastication, which confirmed our approach used for first-bite modelling. Simulation results show the growth of internal stress following the jaw’s path. Presented models demonstrate that the highest values are around teeth pressure and lead to a conclusion that upon biting, the meat structure will suffer irreversible damage dividing the grilled meat into two pieces, as it happens during the first bite. The main conclusion of this study is that by combining results from oral processing and testing of mechanical properties of the grilled products, it is possible to simulate the first bite.